A Qualitative Genre Analysis of Engineering Students' Job Application Letters: A Philippine-Based Study - Mariel Baron; Juliet Caballero; Quenie Marie Maximo; Marry Joyy Solmayor; Ruel Bonganciso; John Jonathan Normandia (Journal of English as A Foreign Language Teaching and Research, 2025)
Despite progressive research on professional communication, the intricacies of job application letter writing among Filipino engineering students remain underexplored. Crafting job application letters varies across different cultures. Factors such as environmental setting, social norms, and deeply held personal beliefs affect their standard structure. Existing studies indicate a scarcity in discipline-specific investigations that fail to emphasize the structure of job application letters of Filipino engineering students and the cultural factors that influence them. Recognizing this gap, the study provides new insights into the particular move-step structures used in job application letters by Filipino engineering students from state universities and colleges in Negros Occidental. For a more distinct analysis, researchers employed a comprehensive mixed-methods content analysis and Bhatia’s (1993) seven-move framework to identify different move-step elements, both obligatory and optional.  Researchers examined 40 job application letters gathered from various state universities and colleges. Through the frequency assessment technique, the study’s novel findings revealed obligatory moves (M1: Establishing credentials; M2: Introducing candidature; M4: Enclosing documents; M6: Soliciting response; M7: Ending politely) labeled as the “universal generic structure”. Meanwhile, optional moves M3 (Offering incentives) and M5 (Using pressure tactics) were omitted, reflecting the socio-cultural setting. This study not only sheds light on the existing conventions among Filipino engineering students but also contributes significantly to the broader discourse on professional communication practices that can enhance employability, sociolinguistic awareness, and discipline-specific templates.